Design Innovation and Fashion Cycles - Wolfgang Pesendorfer (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
A model of fashion cycles is developed in which fashion is used as a signalling device in a "dating-game". We assume that there is a designer (monopolist) who can create new designs at a positive fixed cost and zero marginal cost. Designs are durable commodities. We show the existence of equilibria of the following form: Every T periods a new design is innovated. Over time the price of the design falls and it spreads to more and more agents. Once sufficiently many agents own the design it is profitable to create a new design and a new fashion cycle begins. We also examine the case when there is competition among potential deisigners and show that there are equilibria in which fashion changes less frequent and the price of fashion remains bounded above the corresponding price in the monopoly case.
Keywords: 330